IN VITRO ANTIOXIDANT ACTIVITY OF PHYLLODIUM PULCHELLUM L. DESV - AN THREATENED MEDICINAL PLANT - VELMURUGAN, GOPAL; Parvathi Anand, Subramaniam (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Â Â Objectives: In this study, we determined the in vitro antioxidant capacity of Phyllodium pulchellum of aqueous, ethanol, and chloroform leaf extracts. Methods: In this context, the in vitro antioxidant activity was demonstrated by 2,2-diphenyl-1-picrylhydrazyl (DPPH), 2,2â€²-azinobis(3- ethylbenzothiazolone-6-sulfonic acid) (ABTS+) radical scavenging assay, the total antioxidant activity of phosphomolybdenum assay and hydroxyl radical scavenging activity in different leaf extracts of P. pulchellum. The antioxidant activity of the extracts was compared to standard ascorbic acid. Results: All the four methods of antioxidant showed good reducing power and reducing capacity with increasing concentration again taking the ethanol leaf extract to the top position. Remarkable of antioxidant activity was observed in ethanol leaf extract on the hydrogen peroxide scavenging activity with the lowest inhibitory concentration 50 values of (155.40 Î¼g/ml) followed by DPPH (432.90 Î¼g/ml) and ABTS+ (524.40 Î¼g/ml). Conclusion: These results suggest that the leaf of P. pulchellum could be a valuable source of new antioxidant properties, from the above results it seen that this plant exhibits pharmaceutical activity. Â